Physicochemical characterization and presence of heavy metals in the trout farming area of Lake Titicaca, Peru - Escobar-Mamani, Fortunato; Moreno-Terrazas, Edmundo; Siguayro- Mamani, Humberto; Argota Pérez, George (Universitas Sebelas Maret, 2023)
Certain areas of Lake Titicaca exhibit signs of contamination from urban drainage, mining tailings, and waste from trout cage farming. The objective of this study was to determine the physicochemical conditions of the water and the concentration of heavy metals in sediments of a trout (Oncorhynchus mykiss) farming area in Puno Bay, Lake Titicaca. Water samples were collected at depths of 1, 5, 10, and 15 meters from the surface, as well as from sediments at the bottom of the lake. Additionally, samples were taken 500 meters from the trout breeding area, where no farming activities took place. The study was carried out over a period of 10 months. Some physical-chemical measurements were taken in situ using a multiparametric device, while others were carried out at IMARPE’s laboratory. The results indicate that the physical-chemical quality of the water does not exceed the tolerance limits recommended by the Environmental Quality Standards - ECA Peru. The water pH was 8.79 and the dissolved oxygen was 6.81. The heavy metals (Hg, Cd, Pb, Zn, Cu) found in the sediments were within the permissible limits compared to the ISQG Canada Standard. However, the concentration of As, at 41 mg kg-1, exceeded the tolerance limit. Uncontrolled trends in trout production volumes could compromise water quality and sustainability.